The Impact of Service Quality on Cooperative Customer Satisfaction (Case Study: of Jakarta Cooperatives) - Yudhatama, Ricky; Rismayadi, Budi; Sumarni, Neni (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
Cooperatives have provided quality service for their members but the steps taken by cooperatives for members are not very easy, over time it has provided the best service benefits for members, and some members disagree with providing services and some agree to give service. The research method used in this study is a qualitative method which is useful for providing facts and data. Then the techniques used by researchers are source triangulation techniques, data collection technique triangulation, and time triangulation. In this study, the Jakarta Cooperative of educators and education staff has explained the analysis of service quality and satisfaction of cooperative members, expert judgment on service quality must be made on all services available at cooperatives, service treatment and satisfaction of cooperative members must be (equalized) both Honorary, civil servants as well as government employees with work agreements. Meanwhile, all members, employees, and administrators to further enhance the cohesiveness of togetherness to advance the cooperation of educators and education staff in Jakarta.